Analisis Yuridis terhadap Sanksi bagi Pelaku Child Grooming - Restu Tri Febriana; Ronny Winarno; Wiwin Ariesta (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2026)
This study analyzes the imposition of fair criminal sanctions on perpetrators of child grooming and formulates appropriate legal protection measures to prevent such offenses. It employs normative legal research using statutory and conceptual approaches. Primary, secondary, and tertiary legal materials were collected through a literature review and analyzed qualitatively. The findings indicate that child grooming has not been specifically formulated as a distinct criminal offense under Indonesian law. Criminal liability depends on whether the conduct satisfies the elements of sexual exploitation, pornography, sexual violence, or other offenses regulated by relevant legislation. Criminal sanctions should reflect justice for victims, legal utility through prevention and recovery, and legal certainty for law enforcement authorities. Preventive protection includes education, digital literacy, family communication, school supervision, and community involvement. Repressive protection comprises law enforcement, legal assistance, restitution, identity protection, and social and psychological rehabilitation. The study concludes that clearer provisions concerning the definition, elements, electronic evidence, and sanctions for child grooming are necessary to strengthen child protection and reduce inconsistent legal interpretation. An integrated approach is essential because punishment alone cannot prevent grooming or fully restore the rights and well-being of child victims.